Gender equity in Senegal’s forest governance history: Why policy and representation matter - Bandiaky-Badji, S. (2011)
This paper highlights the ways that gender analysis has been ignored in the development of forestry and land policy in Senegal. The development of local governance/ rural councils through history and their increased decision-making power that occurred with the 1996 decentralization/ regionalization did not take into account the ways that women’s representation (or lack of) on these councils would affect women’s ability to access needed resources. This gender policy analysis paper is guided by two main questions: do the main decentralization reforms, which aim for the principles of equity, accountability, ownership and local participation, promote gender equity and tenure rights in access to land and forest resources? How are the forest and land laws and policies gendered and right-based? I argue that, the lack of adequate gender analysis, consideration of local communities’ rights, and of accountability mechanisms in forest and land policy reforms is due to the low participation and representation of women in political institutions such as political parties, in legislature, and in local governments and to the fact that the forest sector is not gender sensitive. These traditionally male dominated national and local government institutions are the main causes of inequity and exclusion of marginalized groups mainly women in land and forest governance both at the policy and practical level. As long as forest and land policies remain ungendered and do not have a rights-based approach, women will always be legally and socially marginalized from decision making and benefits from forest and land resources. Before advocating for gender equity and women’s rights and tenure in practice, it is necessary and a pre-requisite to have clearly defined gendered national forest and land laws and policies, effective participation and representation of women in political institutions, and gendered accountability mechanisms to hold political leaders, government and local government officials accountable if they fail in practice to recognize women’s ownership rights to land and forest resources.